Az „Ószláv nyelv” című egyetemi tankönyv (1968) fél évszázad távlatából - Zoltán András; Золтан Андраш; Zoltan Andras (II. RF KMF-„RIK-U” Kft., 2020)
Abstract. Emil Baleczky’s extensive knowledge on Slavistics and general linguistics made him suitable for writing a textbook on Old Slavonic. The co-author of the textbook was Attila Hollós, the young colleague and student of Baleczky. The textbook, which was published in 1968, determined the Hungarian university education in Slavic studies for a long time. The textbook is still usable, though of course it bore some restrictions of the age, for example, the name of the language discussed, according to the contemporary Soviet Union’s model became Old Slavonic what was the opposite of the Hungarian tradition (Old Church Slavonic), furthermore Nikolai Trubetzkoy’s periodization of the Slavic language histories, which placed the end of the ancient Slavic period to the 12th century, was mentioned in the textbook, but it was rejected without any argument. It is presumable that the behavior of the Hungarian Slavists in this respect was also determined by the attitude of the official Soviet Union to the emigrated Prince Trubetzkoy. However, the textbook is still scientifically sound and should be republished after the necessary corrections and updates.

Baleczky Emil (1919–1981) igen széles spektrumot átfogó szellemi örökségét mind a szláv világ, mind a magyar tudományos élet nagyra becsüli. Ifjúkori szépirodalmi munkásságának összegyűjtésére egy korábbi konferencia (Budapest, 2007; anyagát l. Материалы 2009) alkalmából tettünk kísérletet (Baleczky 2007, vö. Bárányné 2009a). Tudományos munkássága ugyan a nyelvtudomány területén bontakozott ki, de a szépirodalom iránti érdeklődése mindvégig megmaradt (vö. Hadrovics 1980: 232, valamint Lebovics Viktória és Lyavinecz-Ugrin Mariann tanulmányait ugyanebben a kötetben). Nyelvtudományi munkásságát az utóbbi években Bárányné Komári Erzsébet tanulmánysorozatban elemezte (2009b, 2014, 2015, 2018, 2019a, 2019b), de ukrán kutatók érdeklődését is felkeltette (Сугоняк 2017); életműve szilárdan beépült az ukrán nyelvtudományba (vö. Хланта 2003, Чучка 2007).
http://real.mtak.hu/116621/1/BALECZKYZoltan.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008462
https://kmf.uz.ua/wp-content/uploads/2020/11/final-baleczky_kotet_2020-10-28.pdf
Keywords: Ószláv nyelv; egyetemi tankönyv; Baleczky Emil